The Pastoral Epistles with Philemon & Jude - Saarinen, Risto (Grand Rapids, Mich. : Brazos Press, 2008)
Publisher's description: The Brazos Theological Commentary on the Bible enlists leading theologians to read and interpret scripture creedally for the twenty-first century, just as the church fathers, the Reformers, and other orthodox Christians did for their times and places. The Pastoral Epistles with Philemon & Jude is the seventh volume in the series. This commentary, like each in the series, is designed to serve the church - through aid in preaching, teaching, study groups, and so forth - and demonstrate the continuing intellectual and practical viability of theological interpretation ofthe Bible.
Introduction to the pastoral epistles -- First Timothy. Introductory part (l Tim. 1:1-20) -- Worship, life, and order in the church (1 Tim. 2: 1-3: 16) -- Instructions for the pastoral work of Timothy (1 Tim. 4: 1-6:2) -- True and false teachers (1 Tim. 6:3-21) -- Second Timothy. Opening of the letter (2 Tim. 1:1-5) -- Witness and suffering in the footsteps of Paul (2 Tim. 1:6-2:13) -- False teachers and their conduct (2 Tim. 2: 14-3:9) -- Concluding advice to Timothy (2 Tim. 3:10-4:22) -- Titus. Appointment of elders in Crete (Titus 1: 1-16) -- Virtues among Christians (Titus 2:1-15) -- Good works in the society (Titus 3: 1-15) -- Philemon. Introduction to Philemon -- Jude. Introduction to Jude -- After the word: hermeneutical postscript -- Appendices. A. Moderation of emotion -- B. Mental disorders -- C. Varieties of giving.
Includes bibliographical references (p. 257-262) and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries